The Objective and Subjective Scope of Direct Prosecution in Omani and Palestinian Legislations: A Comparative Study - Al-Waleed, Saher Ibrahim; Al-Azri, Juma’a Musallam (Journal of Posthumanism, 2025)
This research discusses the substantive and personal scope of direct prosecution, through which a public lawsuit may be initiated outside its traditional path represented by the public prosecution (as the representative of society in seeking the right to punish the offender). The study compares these scopes in both the Omani and Palestinian legal systems, and in other legal systems worldwide wherever relevant. The central research problem is expressed in the following question: To what extent are the goals of criminal justice achieved within the substantive and personal scopes for individuals to initiate criminal proceedings through direct prosecution in both Omani and Palestinian criminal justice systems? This research aims to highlight the importance of providing broader substantive and personal scopes for initiating public lawsuit via direct prosecution than currently found in Omani and Palestinian laws, to ensure the achievement of criminal justice. Despite the effective role played by the public prosecution in initiating public actions and ensuring society's right to punish offenders, many cases may go unaddressed due to negligence or failure by this judicial body, which undermines criminal justice, equality before the courts and law, and allows many offenders to escape punishment, depriving victims and society of justice and stability. The study employed descriptive, critical analytical, and comparative methodologies to describe, analyze, and compare the provisions of Omani and Palestinian legislations and related studies, alongside scholarly literature and relevant case law, ultimately achieving the research objectives. The study concludes the necessity of amending Omani, Palestinian, and many other legislations to provide a broader substantive scope allowing the initiation of action in any crime neglected or ignored by the public prosecution, rather than limiting it to one crime as in Omani law. Additionally, it recommends granting the right to initiate such actions not only to those harmed but also to victims, even if they are not directly harmed by the crime.